The fatty acids of human depot fat - L.H. Krut; B. Bronte-Stewart (Journal of Lipid Research, 1964)
The depot fat fatty acid composition has been analyzed in apparently healthy White, Cape Coloured, and Bantu males and females in the third and fifth decades of age and in White males in the fifth decade with proved ischemic heart disease. Comparisons have been made between the ages, between the sexes, and between the races.There was no effect of age on depot fat composition, despite different trends with age between the groups in serum cholesterol concentration and the trend for the degree of body fatness to increase with age in all groups. Females showed higher ratios of monounsaturated to saturated fatty acids than did males.Interracial differences were confined to myristate, which showed a progressive fall from White through Cape Coloured to Bantu that was strikingly correlated with the total fat intake in these groups, and linoleate, which was significantly higher in the Cape Coloured than in either of the other groups. We could find no dietary factor to account for the latter finding.